Dynamic current steering with phantom electrode in cochlear implants - Luo, Xin; Garrett, Christopher (Hearing research, 2020)
Phantom electrode (PE) stimulation can extend the lower limit of pitch perception with cochlear implants (CIs) by using simultaneous out-of-phase stimulation of the most apical primary electrode and the adjacent basal compensating electrode. The total electrical field may push the excitation pattern beyond the most apical electrode to elicit a lower pitch, depending on the ratio of current between the compensating and primary electrodes (i.e., the compensation coefficient σ). This study tested the hypothesis that dynamic current steering of PE stimuli can be implemented by varying σ over time to encode spectral details in low frequencies. To determine the range of σ for current steering and the corresponding current levels, Experiment 1 tested CI users’ loudness balance and pitch ranking of static PE stimuli with σ from 0 to 0.6 in steps of 0.2. It was found that the equal-loudness most comfortable level significantly increased with σ and can be modeled by a piecewise linear function of σ. Consistent with the previous findings, higher σ elicited either lower or similar pitches without salient pitch reversals than lower σ. Based on the results of Experiment 1, Experiment 2 created flat, rising, and falling pitch contours of 300–1000 ms using dynamic PE stimuli with time-varying σ from 0 to 0.6 and equal-loudness current levels. In a pitch contour identification (PCI) task, CI users scored 80% and above on average. Increasing the stimulus duration from 300 to 1000 ms slightly but did not significantly improve the PCI scores. Across subjects, the 1000-ms PCI scores in Experiment 2 were significantly correlated with the cumulative pitch-ranking sensitivity in Experiment 1. It is thus feasible to use dynamic current steering with PE to encode low-frequency pitch cues for CI users. •We tested phantom electrode (PE) stimuli of compensation coefficient σ from 0 to 0.6.•Higher σ needed more current for equal loudness and elicited lower or similar pitches.•Pitch contours were created by dynamically steered PE stimuli with time-varying σ.•Pitch contour identification did not significantly improve with durations > 300 ms•Cumulative pitch-ranking sensitivity may predict pitch contour identification scores.